PROGRAM KEGIATAN MASYARAKAT PETANI MELALUI KEGIATAN PEMBUATAN PUPUK ORGANIK CAIR (POC) DARI KEONG MAS - Ahmad Fadli; Wardatul Jannah; Rosdiana Eka Juniyati; Hermansyah Hermansyah (FKIP Universitas Samawa, 2021)
Community service activities carried out in Banjar Sari Hamlet, West Aikmel Village, Aikmel District, East Lombok Regency, West Nusa Tenggara through counseling to farmers about making liquid organic fertilizer from golden snails. The objectives of this activity are 1. To provide understanding and skills for the farming community to maximize organic fertilizers rather than chemical fertilizers, 2. To provide skills to farmers to use golden snails into organic fertilizers which have been considered by farmers as pests, 3. Help increase farmers' income from the agricultural sector. The method used in this service is the method of socialization, discussion and training on how to make liquid organic fertilizer. The results obtained from this extension activity were that the farmers who participated in the extension were able to make liquid organic fertilizer from golden snails and how to apply it.